Codeine dispensing for privately insured children in the USA: a retrospective database study - Molly M Jeffery; Lucas Oliveira J e Silva; Fernanda Bellolio; Ronna L Campbell; Jana L Anderson (BMJ Publishing Group, 2021)
In this retrospective study using claims data from the OptumLabs Data Warehouse including 24 658 769 eligible person-years of coverage in the USA, there was substantial decline in codeine dispensing between 2010 and 2019. However, we also observed a persistence of codeine prescribing despite the FDA contraindication in 2018. In 2019, codeine was still being prescribed to children aged 12-17 years at 934 prescriptions per 100 000 person-years of coverage and 106 per 100 000 person-years of coverage in children aged<12 years.